The epidemiology of heterophyidiasis in selected areas in Negros Oriental. - Caro, Flora A.
An epidemiological study on heterophyidiasis was conducted in Negros Oriental to determine the eating habits of subjects; identify fish harboring parasites' metacercariae, and the heterophyid species present in the area. Stool specimens from 20 cases identified by U.S. Naval Medical Research Unit-2 (1978) and their families were examined by acid-ether concentration technique. Subjects were interviewed to gather information about their eating habits. 32 fish species were dissected, and metacercariae found were fed to laboratory animals. Adult worms recovered were identified to species. Out of 107 subjects examined, 24 or 22.4 were positive for heterophyid eggs. From interview, it was found out that the following fish species eaten raw or half cooked, and which upon dissection were found infected with metacercariae include: Anabas testudineus, Chanos chanos, Epinephelus corallicola, Gerres filamentosus, G. oyena, Glossogobius giurus, Mugil dussumieri, Pelates quadrilineatus, Scatophagus argus, Siganus canaliculatus, s. Guttatus, Therapon jarbua, and Tilapia nilotica. Experimental infection of laboratory animals with metacercariae from infected fish recovered adult heterophyids such as Haplorchis yokogawai, H. taichui, H. calderoni, Haplorchis sp. 1, 2, and 3, Diorchitrema pseudocirrata, Heterophyopsis expectans, Stictodora manilensis, and s. tanayensis.